2011
DOI: 10.1186/1746-1596-6-102
|View full text |Cite
|
Sign up to set email alerts
|

Mucins Differently Expressed in Various Ampullary Adenocarcinomas

Abstract: BackgroundWe investigated the occurrence and clinical significance of mucin expression in ampullary adenocarcinoma.MethodsWe retrospectively analyzed clinical, pathological, and survival data from 74 ampullary adenocarcinoma patients who received radical operation from January 2004 to November 2006.ResultsThe tumors were located in the lower end of the common bile duct (46%), papillary duodenum (42%), and ampullary duodenum (12%), and expressed MUC1 (72%), MUC2 (20%), MUC5AC (43%), and MUC6 (27%). Expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…It has however previous been shown that the morphological distinction between intestinal and pancreatobiliary morphology has prognostic implications, not only in ampullary adenocarcinomas, but in all periampullary adenocarcinomas, regardless of tumour origin [ 14 ]. Moreover, while differences in the expression of cytokeratins and mucins according to morphology have been observed in ampullary carcinomas [ 15 ], these differences seem to be less evident in series stratified solely by the anatomical centre of the ampullary adenocarcinomas [ 16 ]. These findings suggest that morphological and molecular tumour characteristics have a greater prognostic impact than the appreciated tumour origin.…”
Section: Discussionmentioning
confidence: 99%
“…It has however previous been shown that the morphological distinction between intestinal and pancreatobiliary morphology has prognostic implications, not only in ampullary adenocarcinomas, but in all periampullary adenocarcinomas, regardless of tumour origin [ 14 ]. Moreover, while differences in the expression of cytokeratins and mucins according to morphology have been observed in ampullary carcinomas [ 15 ], these differences seem to be less evident in series stratified solely by the anatomical centre of the ampullary adenocarcinomas [ 16 ]. These findings suggest that morphological and molecular tumour characteristics have a greater prognostic impact than the appreciated tumour origin.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MUC1 is related to poor prognosis in pancreatobiliary pancreatic head tumors. The expression of MUC5AC is associated with good prognosis and little vascular invasion of PDAC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mucins and CDX2 are useful markers for diagnosing ampullary adenocarcinoma and particularly for determining the degree of malignancy (12). Most intestinal-type ampullary cancers express CDX2 and MUC2, whereas pancreatobiliary subtype papillae are, at least focally, positive for MUC5AC, and gastric-tubular subtype papillae are, at least focally, positive for MUC1 (3,11,13).…”
Section: Discussionmentioning
confidence: 99%
“…MUC5AC in our case was positive in only part of the duodenal epithelium, not the site of adenocarcinoma in situ , as we assume our case was an intraepithelial cancer, not an advanced ampullary adenocarcinoma. Patients with ampullary adenocarcinoma positive for MUC5AC have a worse survival than those negative for MUC5AC (12,13).…”
Section: Discussionmentioning
confidence: 99%